2020
DOI: 10.1080/02640414.2020.1812195
|View full text |Cite
|
Sign up to set email alerts
|

The association of the ACTN3 R577X and ACE I/D polymorphisms with athlete status in football: a systematic review and meta-analysis

Abstract: The association of the ACTN3 R577X and ACE I/D polymorphisms with athlete status in football: a systematic review and meta-analysisThe aim of this review was to assess the association of ACTN3 R577X and ACE I/D polymorphisms with athlete status in football and determine which allele and/or genotypes are most likely to influence this phenotype via a meta-analysis. A comprehensive search identified 17 ACTN3 and 19 ACE studies. Significant associations were shown between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 78 publications
1
36
1
Order By: Relevance
“…Several genes have been associated with endurance sports and phenotypes in terms of muscle functioning ( ACTN3 and the c.1729C > T polymorphism) or blood pressure regulation ( ACE and I/D polymorphism) with substantially high replication in multiple cohorts. Specifically, several studies have found that elite endurance athletes with the TT genotype in the ACTN3 or with the DD genotype in the ACE are more frequent than in control populations of untrained individuals or have higher values of variables associated to endurance exercise performance than their counterparts with TT/CT or II/ID genotypes (Ma et al 2013 ; McAuley et al 2021 ; Vaughan et al 2016 ; Miyamoto-Mikami et al 2018 ); however, other studies have not found any effect of the ACTN3 and ACE genotypes on endurance exercise performance (Papadimitriou et al 2018 ; Mägi et al 2016 ). Additionally, the genetic component for the observed variability of muscle fiber types in humans is ~ 40–50%, indicating that muscle fiber-type composition is determined equally by genotype and environment (Ahmetov et al 2012 ).…”
Section: Sports Performancementioning
confidence: 99%
“…Several genes have been associated with endurance sports and phenotypes in terms of muscle functioning ( ACTN3 and the c.1729C > T polymorphism) or blood pressure regulation ( ACE and I/D polymorphism) with substantially high replication in multiple cohorts. Specifically, several studies have found that elite endurance athletes with the TT genotype in the ACTN3 or with the DD genotype in the ACE are more frequent than in control populations of untrained individuals or have higher values of variables associated to endurance exercise performance than their counterparts with TT/CT or II/ID genotypes (Ma et al 2013 ; McAuley et al 2021 ; Vaughan et al 2016 ; Miyamoto-Mikami et al 2018 ); however, other studies have not found any effect of the ACTN3 and ACE genotypes on endurance exercise performance (Papadimitriou et al 2018 ; Mägi et al 2016 ). Additionally, the genetic component for the observed variability of muscle fiber types in humans is ~ 40–50%, indicating that muscle fiber-type composition is determined equally by genotype and environment (Ahmetov et al 2012 ).…”
Section: Sports Performancementioning
confidence: 99%
“…The analysis of the impact of COVID-19 on injury incidence in female football players is another key element to be studied to understand the true effect of COVID-19 on professional football. Third, only epidemiological data were analysed, not considering other factors that could trigger the apparition of injury, such as perceived fatigue, wellness [ 29 , 30 ] or some genetic variants [ 31 , 32 ]. Despite these limitations, we believe that the investigation contributes to the current knowledge of the effect of COVID-19 on the incidence and characteristics of injuries in male professional football.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to their small effect sizes and consequent lack of explained inter-individual variance between athletes and controls [4]. For example, a recent review meta-analysed the most studied genetic variants associated with athlete status in football (i.e., ACTN3 R577X and ACE I/D), which reported only modest allelic odds ratios of 1.18-1.35 [18]. In the future, it is also highly unlikely any genetic variant, or polygenic profile, will ever have the specificity/sensitivity to solely predict future sporting prowess [24,36].…”
Section: Discussionmentioning
confidence: 99%